Histomorphology of the pancreas in myna - S. Rajathi; S. Muthukrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Histological study was performed in the pancreas of two adult male mynas. Tissue pieces from different lobes of pancreas were fixed and processed in routine manner. Four to Five micron thick sections were stained using Haematoxylin and Eosin staining technique. The present study observed that the histological study of the pancreas in Myna consisted of exocrine acinar portion with ducts and endocrine diffuse portion with no connective tissue separation between them. The pancreas was covered by a thin connective tissue capsule which consisted of collagen, elastic and reticular fibres. The parenchyma was divided into lobes and lobules by connective tissue septa from the capsule. The exocrine acini were round to oval in shape. The acinar cells were columnar to polygonal in shape with apical eosinophilic large granules and basally dark cytoplasm with oval nucleus. The duct system started with intercalated, intralobular, interlobular, intralobar and large ducts which were lined by simple squamous, simple cuboidal, simple columnar, stratified cuboidal and stratified columnar cells, respectively. Centroacinar cells were absent. The endocrine portion consisted of lightly stained cells with different shapes. The nucleus of these cells was also compact in some cells and vacuolated in some cells. Numerous sinusoids were found between the acini.